The predictors of long-COVID in the cohort of Turkish Thoracic Society- TURCOVID multicenter registry: One year follow-up results - Baris, Serap Argun; Toprak, Oya Baydar; Cetinkaya, Pelin Duru; Fakili, Fusun; Kokturk, Nurdan; Kul, Seval; Bayram, Hasan (Wolters Kluwer Medknow Publications, 2022)
Objective: To evaluate long-term effects of COVID-19, and to determine the risk factors in long-COVID in a cohort of the Turkish Thoracic Society (TTS)-TURCOVID multicenter registry.Methods: Thirteen centers participated with 831 patients; 504 patients were enrolled after exclusions. The study was designed in three-steps: (1) Phone questionnaire; (2) retrospective evaluation of the medical records; (3) face-to-face visit. Results: In the first step, 93.5% of the patients were hospitalized; 61.7% had a history of pneumonia at the time of diagnosis. A total of 27.1% reported clinical symptoms at the end of the first year. Dyspnea (17.00%), fatigue (6.30%), and weakness (5.00%) were the most prevalent long-term symptoms. The incidence of long-term symptoms was increased by 2.91 fold (95% CI 1.04-8.13, P=0.041) in the presence of chronic obstructive pulmonary disease and by 1.84 fold (95% CI 1.10-3.10, P=0.021) in the presence of pneumonia at initial diagnosis, 3.92 fold (95% Cl 2.29-6.72, P=0.001) of dyspnea and 1.69 fold (95% Cl 1.02-2.80, P=0.040) fatigue persists in the early-post-treatment period and 2.88 fold (95% Cl 1.52- 5.46, P=0.001) in the presence of emergency service admission in the post COVID period. In step 2, retrospective analysis of 231 patients revealed that 1.4% of the chest X-rays had not significantly improved at the end of the first year, while computed tomography (CT) scan detected fibrosis in 3.4%. In step 3, 138 (27.4%) patients admitted to face-to-face visit at the end of first year; at least one symptom persisted in 49.27% patients. The most common symptoms were dyspnea (27.60%), psychiatric symptoms (18.10%), and fatigue (17.40%). Thorax CT revealed fibrosis in 2.4% patients. Conclusions: COVID-19 symptoms can last for extended lengths of time, and severity of the disease as well as the presence of comorbidities might contribute to increased risk. Long-term clinical issues should be regularly evaluated after COVID-19.
Keywords: Long COVID-19; Dyspnea; Fatigue; Comorbidity